PENGARUH PENDIDIKAN KESEHATAN TENTANG MANAJEMEN ASI PERAH MELALUI MEDIA BOOKLET PADA IBU BEKERJA DI RSUP DR.RIVAI ABDULLAH TAHUN 2022 - Lisda Maria; Heriana Musyafira (Jurnal Kesehatan dan Pembangunan, 2023)
Background: Breast milk has important nutrients and is beneficial for the growth and development of infants and recommends exclusive breastfeeding until the child is 6 months old. Working mothers generally fail to fulfill due to difficulties in managing expressed breast milk caused by lack of knowledge. The results of the survey at RSUP DR. Rivai Abdullah showed that knowledge was lacking. Objective: to determine the effect of health education on the management of expressed breast milk through booklet media for working mothers at RSUP Dr. Rivai Abdullah in 2022. Methods: This type of research is a quasi-experimental in which the form of design used is quasi-experimental. used is a one group pretest-posttest design. all working mothers who became inpatients and obstetric polyclinics at Dr. Rivai Abdullah Hospital Palembang in the period March 2022 with a total sample of 25 people. Data analysis used paired T test. Results: The average knowledge of respondents about the management of expressed breast milk in working mothers before being given health education was 50.40 (11.71) and increased to 76.40 (11.68). The average increase in respondents' knowledge about the management of expressed breast milk was 26.0 (10.40) after the intervention. The results of the statistical test showed P value = 0.000 ; 9% CI 21.704 - 30.296 which indicated a significant difference before and after the study. Conclusion: There is an effect of health education on Dairy ASI Management on knowledge of working mothers at Dr. RSUP. Rivai Abdullah in 2022 (P value = 0.000 ; 9% CI 21.704 – 30.296). Suggestion: it is recommended to develop a model of health education on breast milk with a wider scope for working mothers from pregnancy to the puerperium. Keywords: Knowledge, Expressing breast milk, working mother